Contrasting host immuno‐inflammatory responses to bacterial challenge within venous and diabetic ulcers. Issue 1 (13th December 2013) - McInnes, Rachael L.; Cullen, Breda M.; Hill, Katja E.; Price, Patricia E.; Harding, Keith G.; Thomas, David W.; Stephens, Phil; Moseley, Ryan
Abstract Within chronic wounds, the relationship between the clinical diagnosis of infection and bacterial/immuno‐inflammatory responses is imprecise. This study prospectively examined the interrelationship between clinical, microbiological, and proinflammatory biomarker levels between chronic venous leg ulcers (CVLUs) and diabetic foot ulcers (DFUs). Wound swabs and fluids were collected from CVLUs (n = 18) and DFUs (n = 15) and diagnosed clinically as noninfected or infected; and qualitative/quantitative microbiology was performed. CVLU and DFU fluids were also analyzed for cytokine, growth factor, receptor, proteinase/proteinase inhibitor; and oxidative stress biomarker (protein carbonyl, malondialdehyde, and antioxidant capacity) levels. While no correlations existed between clinical diagnosis, microbiology, or biomarker profiles, increasing bacterial bioburden (≥107 colony‐forming unit/mL) was associated with significant alterations in cytokine, growth factor, and receptor levels. These responses contrasted between ulcer type, with elevated and decreased cytokine, growth factor, and receptor levels in CVLUs and DFUs with increasing bioburden, respectively. Despite proteinase biomarkers exhibiting few differences between CVLUs and DFUs, significant elevations in antioxidant capacities correlated with increased bioburden in CVLU fluids, but not in DFUs. Furthermore, oxidative stress biomarker levels were significantly elevated in all DFU fluids compared with CVLUs. This study provides further insight into the contrasting disease‐specific host responses to bacterial challenge within infected CVLUs and DFUs.